Fourteen- to Eighteen-Month-Old Infants Use Explicit Linguistic Information to Update an Agent’s False Belief - Jin, Kyong-Sun; Kim, Yoon; Song, Miri; Kim, Yu-Jin; Lee, Hyuna; Lee, Yoonha; Cha, Minjung; Song, Hyun-Joo (Frontiers in Psychology, 2019)
The present research examines how infants use linguistic information to update an agent’s false belief about an object’s location. Fourteen- to 18-month-old infants first watched a series of events involving two agents, a ball, and two containers (a box and a cup). Agent1 repeatedly played with the ball and then put it in the box in the presence of agent2. In agent1’s absence, agent2 switched the ball’s location from the box to the cup. When agent1 returned, agent2 told her, “The ball is in the cup!” Agent1 then reached for either the cup (cup event) or the box (box event). The infants looked reliably longer if shown the box event as opposed to the cup event. However, when agent2 simply said, “The ball and the cup!”, which does not provide explicit information about the ball’s new location, infants looked reliably longer if shown the cup event as opposed the box event. These findings thus provide new evidence for false-belief understanding in infancy and suggest that infants expect an agent’s false belief to be corrected only by explicit verbal information.